South Korea HD Hyundai machinery used in West Bank demolitions - Amnesty International (Amnesty International, 2025)
HD Hyundai machinery has been widely used in demolitions of Palestinian-owned structures in the Occupied Palestinian Territory (OPT), according to new visual and testimonial evidence documented by Amnesty International Korea and local human rights groups.
South Korea